1977
DOI: 10.4315/0362-028x-40.9.614
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characterization of Human Milk

Abstract: Milk samples of five breast-feeding mothers were studied for bacterial population, flora, and source. In most instances, samples taken at postfeeding contained higher bacterial populations than prefeeding samples. Staphylococcus epidermidis was the predominant organism isolated from 100% of the samples. Increases were noticed in the appearance of Streptococcus mitis, Gaffkya tetragena, Streptococcus salivarius, Staphylococcus aureus, as well as Lactobacillus acidophilus, in the postfeeding samples. Main source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
2

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…Increases in the number of staphylococci, streptococci, and Lactobacillus acidophilus species after feeding suggest that the infant's mouth is another potential source of bacteria. 5 Furthermore, a study reported that some strains of Lactobacillus gasseri and Enterococcus faecium in milk were identical to those in swabs of the areola and in oral swabs from the infant. 6 It might be argued that such sources of bacteria are also biologically relevant to neonates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increases in the number of staphylococci, streptococci, and Lactobacillus acidophilus species after feeding suggest that the infant's mouth is another potential source of bacteria. 5 Furthermore, a study reported that some strains of Lactobacillus gasseri and Enterococcus faecium in milk were identical to those in swabs of the areola and in oral swabs from the infant. 6 It might be argued that such sources of bacteria are also biologically relevant to neonates.…”
Section: Discussionmentioning
confidence: 98%
“…4 The majority of the latter arise from the mother's skin or the infant's mouth. 4,5 However, certain species are suggested to colonize the neonatal intestine and to provide protection. 6 The interesting observation that breast milk is not sterile, even when collected aseptically, 7 raises the possibility that breast milk harbors a natural bacterial inoculum, which may influence neonatal colonization.…”
mentioning
confidence: 99%
“…Breast milk is seldom sterile, it contains numerous bacteria which may originate from the infant's mouth or mother's skin (Lucas and Roberts, 1979), and if collected under unsanitary conditions may show high bacterial counts. Bacteria in human milk include the potential pathogens Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae (Davidson et al, 1979;Gavin and Ostovar, 1977;Lin et al, 1988). In view of the possibilities of bacterial contamination, some form of heat treatment is considered necessary to ensure microbiological safety of stored human milk (American Academy of Pediatrics Committee on Nutrition, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In sows, Kemper and Preissler (2011) found that coagulase-negative staphylococci and Streptococcus spp were the most frequently isolated bacteria from the teat duct of post-parturient sows, whilst Escherichia coli and Klebsiella aerogenes, the principal porcine mammary pathogens (Jones, 1971). Finally, in women, various studies have shown that milk of healthy individuals was seldom sterile, with the predominant and most frequently isolated bacteria reported to be coagulase-negative staphylococci (Gavin and Ostovar, 1977;West et al, 1979). Since information is not available on the bacterial flora of the udder of does and since this information is germane in the understanding of caprine mastitis, the three investigations described herebelow have been undertaken.…”
mentioning
confidence: 99%